Adolescent Contraceptives - Ara Nasreen, Shaikh Zinnat; Huq, Sabereen; Huq, Saleheen; Shahreen, Safinaz (International Journal of Innovative Research in Medical Science, 2021)
Adolescents contraceptive need to be the top most priority in the national policy to prevent the adolescent pregnancies and it’s adverse consequences. All the countries of the world should have their own national strategy liaison with global consensus regarding the Adolescent contraceptives. Global challenge is to tackle the adolescents Pregnancy. Contraceptives use is the answer. So adolescents should be the centrals to everything we want to achieve, and to the overall success of the 2030 SDG Agenda. Without Contraceptive “SDG achievement” is not possible. About 21 million 15-19 year old girls in developing countries become pregnant every year. Half of these pregnancies (49%) are unintended. If we are successful to implement contraceptives among the youngsters, adolescent’s pregnancy complications can be eliminated. But again this needs strong political motivation and hard work of health care providers. Health care team should design and deliver a Confidential, personalized, adolescent’s friendly service taking into account adolescent's psychosocial & sexual needs. Almost all methods of contraceptives are suitable for adolescents except few. After taking a comprehensive medical history & assessing risk factors counselling should be done for risks & benefits. Good & sensible communication with women, their husband or partner is important. It remains a critical aspect in empowering adolescents to make informed choices and only then adolescents will use contraceptives wholeheartedly.